2009
DOI: 10.1177/0363546508331137
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Model to Study Chondrogenic Differentiation in Tendinopathy

Abstract: This model can be used to investigate chondrogenic differentiation as a possible target for drug treatment, contributing to the development of more successful mechanism-based treatment opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 39 publications
7
66
1
2
Order By: Relevance
“…Increases were noted in the concentrations of PDGF, VEGF, TGF␤, and hepatocyte growth factor (HGF), four growth factors that promote matrix production. A 2008 report indicated that tenocyte proliferation increased when human hamstring tendon fragments were cultured in PRP [20,21]. In another study of human hamstring tendon, PRP increased fibroblast proliferation and VEGF expression by tenocytes [22].…”
Section: Prp Effects On Human Cells and Tendonsmentioning
confidence: 99%
“…Increases were noted in the concentrations of PDGF, VEGF, TGF␤, and hepatocyte growth factor (HGF), four growth factors that promote matrix production. A 2008 report indicated that tenocyte proliferation increased when human hamstring tendon fragments were cultured in PRP [20,21]. In another study of human hamstring tendon, PRP increased fibroblast proliferation and VEGF expression by tenocytes [22].…”
Section: Prp Effects On Human Cells and Tendonsmentioning
confidence: 99%
“…Tendon injuries represent a significant clinical problem, and details of the pathological changes in overloaded tendon and the associated development of tendinopathy are sparse (Arnoczky et al, 2007). Focal histopathological changes have been documented in the region of the overused tendon, including collagen disorganization, increased cellularity, cell rounding and neovascularisation (de Mos et al, 2009). Further it has been shown that expression of both collagen type I, collagen type III, matrix metalloproteinases and other ECM proteins is higher in tendinopathic than in healthy tendon (de Mos et al, 2007, Jones et al, 2006) and that the tissue content of several proteins like versican and aggrecan is upregulated in tendinopathy (Parkinson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chondroid metaplasia has been histologically identified in tissue biopsies of Achilles tendinopathy in humans [16]. A few studies have raised the possibility that native tendon cells may be able to undergo chondrogenic differentiation, and there is evidence for load-dependent regulation of cartilaginous phenotypes within the tendon [17], [18]. Despite the cellular origin or mechanical contribution to the chondroid heterogeneity, the presence of this tendinopathic marker validates degenerative tissue changes in the aged rat model used in this study.…”
Section: Resultssupporting
confidence: 56%